INFORMATION TECHNOLOGIES IN SCIENCE (Web of Technology: Multidimensional Research Journal, 2024)
This article deals with the issues of teaching the basics of electrical engineering and electronics in higher military education on the basis of information and communication technologies. The article also discusses the role of the Project Board layout, its advantages, convenience, use, and interesting organization of practical and laboratory training with the help of this layout board. The layout of the Project Board shows the use of integrated circuits, which are the basis of radio electronics, as well as the advantages of this board over the universal laboratory stand and in conjunction with the program ARDUINO.